Inverse coordinates

Geometry Level 5

A stationary observer is located at the origin of the Cartesian plane. A point moves along the circle whose parametric equation is

p ( t ) = ( 3 + 2 cos t , 4 + 2 sin t ) p(t) = (3 + 2 \cos t ,4 + 2 \sin t)

If we now attach a coordinate frame to the moving point, such that the y y' -axis of the frame is pointing along the tangential of the circle in the direction of motion, while the x x' -axis is pointing along the outward normal to the circle, and we want to describe the resulting curve traced by the stationary observer with respect to this moving frame, what will be this curve ?

A circle with center ( 2 , 0 ) (-2, 0) and radius 5 5 A single point A circle with center ( 2 , 0 ) (2, 0) and radius 5 5 A circle with center ( 3 , 4 ) (-3, -4) and radius 2 2

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Steven Chase
Jul 27, 2019

Coordinates of p p :

p ( t ) = ( 3 + 2 cos t , 4 + 2 sin t ) p(t) = ( 3 + 2 \cos t, 4 + 2 \sin t)

Define the unit tangential and normal vectors:

T = ( sin t , cos t ) N = ( cos t , sin t ) T = (-\sin t, \cos t) \\ N = (\cos t, \sin t)

Position of origin relative to p p :

v = ( 0 p x , 0 p y ) v = (0 - p_x, 0 - p_y)

Express vector v v as a weighted sum of T T and N N :

v = α T + β N v x = α T x + β N x v y = α T y + β N y v = \alpha \, T + \beta \, N \\ v_x = \alpha \, T_x + \beta \, N_x \\ v_y = \alpha \, T_y + \beta \, N_y

Solve the system for α \alpha and β \beta .

α = v y N x v x N y T y N x T x N y β = v x α T x N x \alpha = \frac{v_y N_x - v_x N_y}{T_y N_x - T_x N_y} \\ \beta = \frac{v_x - \alpha T_x}{N_x}

Make a scatter plot of the point ( β , α ) (\beta, \alpha) as the parameter t t varies. It is a circle of radius 5 5 centered at ( β , α ) = ( 2 , 0 ) (\beta, \alpha) = (-2,0) . I have attached simulation code as well.

 1
 2
 3
 4
 5
 6
 7
 8
 9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
import math

dt = 2.0*math.pi/(10.0**3.0)

t = 0.0

while t <= 2.0*math.pi:

    px = 3.0 + 2.0*math.cos(t)
    py = 4.0 + 2.0*math.sin(t)

    #######

    Tx = -math.sin(t)
    Ty = math.cos(t)

    Nx = math.cos(t)
    Ny = math.sin(t)

    #######

    vx = 0.0 - px
    vy = 0.0 - py

    #######

    alpha = (vy*Nx - vx*Ny)/(Ty*Nx - Tx*Ny)
    beta = (vx - alpha*Tx)/Nx

    print beta,alpha

    t = t + dt

Hosam Hajjir
Jul 29, 2019

The unit vector along the direction of motion ( the y y' axis ) is along p ( t ) p'(t) , the time derivative of p ( t ) p(t) . Hence the unit vector along the y y' is ( sin t , cos t ) (-\sin t , \cos t) . Moreover, the x x' axis is along the vector pointing outward from the center of the given circle, so the unit vector of the x x' axis is along ( cos t , sin t ) (\cos t , \sin t ) . This defines our moving reference frame. If r r is a point coordinate in the global reference frame and r r' is the corresponding coordinate in the x y x' y' frame, then

r = p ( t ) + R ( t ) r r = p(t) + R(t) r'

where

R ( t ) = [ cos t sin t sin t cos t ] R(t) = \begin{bmatrix} \cos t && -\sin t \\ \sin t && \cos t \end{bmatrix}

The point of interest is the origin r = 0 r = 0 , and therefore, its coordinate in the x y x' y' frame is

r ( t ) = R 1 ( t ) p ( t ) = R T ( t ) p ( t ) r'(t) = - R^{-1}(t) p(t) = - R^T(t) p(t)

But,

p ( t ) = [ 3 4 ] + 2 [ cos t sin t ] p(t) = \begin{bmatrix} 3 \\ 4 \end{bmatrix} + 2 \begin{bmatrix} \cos t \\ \sin t \end{bmatrix}

Substituting this and R ( t ) R(t) into the r ( t ) r'(t) equation yields,

r ( t ) = R T ( t ) [ 3 4 ] 2 [ 1 0 ] r'(t) = - R^T(t) \begin{bmatrix} 3 \\ 4 \end{bmatrix} - 2 \begin{bmatrix} 1 \\ 0 \end {bmatrix}

The first term produces a rotating vector (in the clockwise direction, because of the transpose operation, which essentially negates the angle parameter t t ) starting at ( 3 , 4 ) (-3, -4) , while the second term is a fixed offset by ( 2 , 0 ) (-2, 0)

Hence, the sought curve is a circle of radius 5 = 3 2 + 4 2 5 = \sqrt{ 3^2 + 4^2} , offset by the center vector ( 2 , 0 ) (-2, 0 ) .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...